2013
DOI: 10.1097/acm.0b013e3182a9262d
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Training Promote or Deter Self-Directed Learning? A Longitudinal Mixed-Methods Study

Abstract: The initial scores indicate high self-direction. The drop in scores one year after admission, and the lack of change with increased training, show that the current educational interventions may require reexamination and alteration to ones that promote SDL. Comparison with schools using a different curricular approach may bring to light the impact of curriculum on SDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
5
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 22 publications
5
60
5
14
Order By: Relevance
“…Failure to learn within the period allotted is also a potential problem. The variability in patient profiles encountered during residency, heavily influenced by the socioeconomic factors in a given geography, also affects the range of skills acquired (2,18,22). Supported self-directed learning methods aim to minimize such undesired effects of self-directed learning and make better use of limited teaching time.…”
Section: Discussionmentioning
confidence: 98%
“…Failure to learn within the period allotted is also a potential problem. The variability in patient profiles encountered during residency, heavily influenced by the socioeconomic factors in a given geography, also affects the range of skills acquired (2,18,22). Supported self-directed learning methods aim to minimize such undesired effects of self-directed learning and make better use of limited teaching time.…”
Section: Discussionmentioning
confidence: 98%
“…Lifelong learning is one of the most emphasized components of being a successful physician. As a promising methodology for lifelong learning, SDL has been recommended in medicine [1][2][3] and has increasingly been emphasized as an important principle in medical education. Several definitions of SDL have been suggested in the literature [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Baskett [13] identified workplace factors that improve SDL and found that effective communication systems, an environment of trust and mutual respect, and collaboration among organization members were all important factors for enhancing SDL. Previous studies have shown that self-directed learning involves interaction with peers and teachers to exchange information [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…The World Federation for Medical Education (WFTE) has endorsed self-directed learning as an important component of medical undergraduate education (19). The ability of future physicians to successfully engage in self-directed learning activities is essential to the development of life-long learning skills, which are necessary to keep pace with the ever changing landscape of medical practice (18). Providing our pipeline students with self-directed learning experiences, under the guidance of an experienced undergraduate medical student, gives them a head start on learning practices necessary for success in medical school and beyond.…”
Section: Discussionmentioning
confidence: 99%